Developing a Comprehensive Leadership Program for Extension County Directors - Brandi C. Berven; Allisen Penn; Janet C. Cluck; Shirley W. Hastings ([TEST] Journal of Extension, 2021)
This article provides an overview of the development and components of LEAD95, UT Extension’s comprehensive leadership program for county-level leaders. The program was designed using results from a Delphi study, which identified critical skills and resources for new county directors to be successful. The program consists of face-to-face workshops, mentoring, a multi-rater assessment, online learning opportunities, and an online resource toolkit. Expected outcomes include increased competency, increased job satisfaction, and more consistent leadership and direction among county-level leaders in the UT Extension system.
Keywords: Leadership development; leadership assessment; professional development; first level leaders; middle managers